(untitled) (Journal of the College of Basic Education, 2026)
Poetic imagination in the works of Adonis and William Wordsworth is one of the most important elements that establish the structure of a poetic text. This is because it is a crucial factor in shaping the textual structure, creating its most profound meanings, and opening new poetic horizons. It is also a structural component in particular, contributing to the generation of the text and the creation of its aesthetic worlds. This helps the reader interpret its details, understand its meanings and implications, and grasp the possible and potential concepts it contains. This research addresses the emotional state through which the poet portrays his thoughts and feelings and conveys them to the reader through vivid imagery and natural imagination, thus transcending the boundaries of reality and presenting new perspectives to the reader and to language. This research aims to describe and analyze the poetic imagination of Adonis and William Wordsworth, and to identify the similarities and differences in their poetic imagination. Using the descriptive-analytical method and the comparative method, selected poems from Adonis’s collection "Songs of Mihyar the Damascene" and Wordsworth’s "Collected Reading Texts from the Cornell Wordsworth Series" were analyzed and compared. The research reached the following key findings: the poetic imagination of both Adonis and Wordsworth extends beyond imaginative, symbolic, and mythical imagery, indicating a close connection between their content and psychological states. The similarities and differences lie in the clear and highly professional use of imaginative ideas. Poetic imagination often served as an escape from painful realities and harsh circumstances in their poems, resulting in exceptionally beautiful and creative imagery. The difference lies in the content and style. Adonis’s poems focused on the linguistic and aesthetic structures of the text, while William Wordsworth did not prioritize these elements to the same degree, concentrating his poems on specific, fixed structural components.